My life in Dire Straits : the inside story of one of the biggest bands in rock history - Illsley, John (Diversion Books, 2021)
Starting with his own unlikely beginnings in Middle England, John Illsley recounts the rise of Dire Straits from humble origins in London's spit-and-sawdust pubs to the best-known venues in the world, the working men's clubs to Madison Square Garden, sharing gigs with wild punk bands to the Live Aid stage at Wembley until, ultimately, the shattering demands of touring on a global scale and living life in the spotlight took their inevitable toll.